664. Factors Associated with the Need for ICU Care Among Patients with Human Ehrlichiosis. (26th November 2018) - Kuriakose, Kevin; Pettit, April; Schmitz, Jonathan; Moncayo, Abelardo; Bloch, Karen
Abstract: Background: Despite the availability of effective therapy, the case fatality rate of human monocytic ehrlichiosis (HME) is 3%, and has been reported to be higher among the immunocompromised. Little is known about predictors of severe disease. Methods: We performed an observational cohort study at a tertiary care medical center in Nashville, TN. Patients with a positive whole blood or cerebrospinal fluid Ehrlichia polymerase chain reaction between 2007 and 2017 were included. Clinical and demographic data were obtained by chart abstraction. Modified Poisson Regression was used to estimate the adjusted relative risk (aRR) of requiring intensive care unit (ICU) care, adjusting for age, sex, race, Charlson Comorbidity Index, immunosuppression, patient-reported tick exposure, and number of days from first contact with healthcare system to treatment initiation. Results: We included 155 patients; median age was 48 years, 64% were male, 94% were Caucasian, 74% reported a tick exposure, and 21% were immunocompromised. 28% of patients required ICU care. Immunosuppression and reported tick exposure were associated with a decreased risk of requiring ICU care. An increasing number of days from first contact with the healthcare system to treatment initiation were associated with an increased risk of requiring ICU care. Conclusion: Twenty-eight percent of patients required ICU care. We found that a delay in initiation of therapy was associated with an increased risk of requiring ICU care. In contrast to other studies, we found immunosuppression to be associated with milder clinical illness, perhaps reflecting a lower threshold to seek care and thus earlier presentation. Patients with recent tick exposure were also less likely to require ICU care, potentially reflecting a higher index of suspicion for HME among providers. Future studies evaluating the impact of provider education on early recognition and treatment may lead to a decreased need for ICU care in patients with HME. Disclosures: All authors: No reported disclosures.